Where East meets West. Mediterranean and northwestern imports in Aguntum, Noricum - Angerer, Christiane; Auer, Martin; Rabitsch, Julia (Rei Cretariae Romanae Fautorum Acta, 2024)
Over the last few years several Eastern Mediterranean imports were detected in the Norican town of Aguntum/Dölsach (Austria). These do not only consist of wine amphorae, but also include fine wares and oil lamps from Corinth as well as Eastern Sigillata B (ESB) and cooking wares from the Phokaia Region. The municipium Aguntum functions as an intersection between the northern and the southern provinces; for that reason, we can find Eastern imports as well as imports from the Northern provinces here. A special find assemblage was discovered in a fire horizon in the traders’ forum that contains ESB and stamped Samian ware from the production centres in Lezoux and Rheinzabern. This assemblage represents the starting point for the present paper. The diverse spectrum of imported pottery in Aguntum will be examined and set in a wider geographical context.